Exploring the interplay of ambidexterity and business model innovation in agrifood international joint-ventures - Cherbib, Jihene; Avila, Joao; Cherni, Maryem (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
This study investigates the drivers of ambidexterity in agrifood international joint ventures (IJVs) and its influence on business model innovation (BMI). Drawing on a longitudinal qualitative case study approach, we analyzed five IJVs between SMEs and multinationals, focusing on the interplay between partner’s innovation orientation (IO), learning orientation (LO) and ambidexterity. The results demonstrate that ambidexterity serves as a critical prerequisite for driving BMI in IJVs. This paper contributes to both the IJV and business model literature, offering new insights into the dynamic processes underlying the role of ambidexterity in driving BMI. For practitioners, our study offers valuable managerial insights by highlighting the importance of strategic alignment, collaborative learning, and adaptive capacity in fostering ambidexterity and ultimately, successful IJV outcomes.